Global Laboratories of Third-Party Funding Regulation - Victoria Shannon Sahani (AJIL Unbound, 2021)
Third-party funding, also known as “dispute finance,” is a controversial, dynamic, and evolving arrangement whereby an outside entity (“the funder”) finances the legal representation of a party involved in litigation or arbitration, whether domestically or internationally, on a non-recourse basis, meaning that the funder is not entitled to receive any money from the funded party if the case is unsuccessful. It has been documented in more than sixty countries on six continents worldwide—including in many of the jurisdictions highlighted in this symposium that are experimenting with other aspects of international commercial dispute resolution. Indeed, funding greases the wheels of this experimentation. The true prevalence of third-party funding is likely far greater than we know since disclosure is not presently mandated everywhere. This essay argues that the three biggest global regulatory issues with respect to dispute finance are disclosure, definition, and delegation of oversight and that the global laboratories of dispute finance remain firmly within the control of the private sector with the public regulators continuously struggling to understand and address new developments in the industry. An apt analogy would be that the dispute financiers are driving cars and building spaceships with respect to their innovative financing arrangements, while many of the regulators are aiming their sights at the classic “horse-and-buggy” third-party funding arrangements that are rapidly falling out of use.